News of Ibn Qutaybah - a study in the cultural pattern - Hassan, Dr. Khalid Sakban (Thi Qar Arts Journal, 2023)
Cultural reading seeks to re-read literary texts in light of their historical and cultural contexts, as the cultural pattern is a social, religious, moral, aesthetic, etc. position imposed by the social situation at a certain moment of its development, which the author and his audience implicitly accept. The texts include in their structure implicit and deceptive patterns capable of evasion and avoidance, and they cannot be revealed or revealed their latent meanings in the literary achievement except by achieving a holistic conception of the nature of the cultural structures of society, and realizing the reality of the dominance of those established patterns on the idea of ideology and the concept of the possible in the conflict of different social forces, which is what This study tends to read the cultural patterns in the book (Eyes of the News) by Ibn Qutaybah. Received 6/6/2023,Accepted 5/8/2023  ,Published 30/9/2023.